Comparative foraging and diving behaviour of coexisting breeding and non-breeding King Penguins (Aptenodytes patagonicus) in Tierra del Fuego, Chile. (2nd January 2019) - Gherardi-Fuentes, Camila; Pütz, Klemens; Anguita, Cristobal; Simeone, Alejandro
ABSTRACT: Breeding status directly affects the at-sea behaviour of seabirds, resulting in marked differences between breeding and non-breeding birds. In this study, we report for the first time the foraging and diving behaviour of coexisting incubating, courting and non-breeding King Penguins ( Aptenodytes patagonicus ) at a recently established colony in Tierra del Fuego, Chile, to determine differences in (1) the number and duration of the foraging trips, (2) time spent at sea and on land, and (3) diving performance and foraging success. We obtained data from four incubating, five courting and three non-breeding penguins equipped with time–depth recorders during November and December 2014. Incubating birds performed a single but long trip (8.1 ± 1.9 days), while courting birds performed one or two trips of intermediate duration (2.3 ± 0.8 days) and non-breeders made multiple short trips (0.6 ± 0.1 days). Courting birds spent a significantly greater proportion of their time on land than the other birds. Incubating birds performed the deepest and longest dives and had the highest diving efficiency, while non-breeders performed the shallowest and shortest dives and exhibited low diving efficiencies, suggesting that birds are utilising different foraging areas. These results indicate that incubating, courting and non-breeding King Penguins, although coexisting temporally at the same colony, differentially adjust their foraging and diving behaviour, most likely to accomplish their specific social and energetic demands.